Pengaruh Pelatihan Microsoft Word, Canva, Dan Persiapan Mental Terhadap SDM: Mediasi Pendidikan Agama Dan Moderasi Lingkungan - Sri Wahyuningsih; Sindik Widati; Catur Sasi Kirono (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
This study aims to evaluate the impact of the integration of technology training and Qur'an literacy in shaping a generation of character in the era of Society 5.0. The research was conducted in Sukadami Village, South Cikarang District, Bekasi Regency, which faces challenges in education and character building. The research uses a qualitative method through a community service approach, with research subjects for elementary to high school students at the equivalent level. The results of the study showed that the combination of technology training, such as the use of Microsoft Word and Canva, with Qur'anic literacy contributed significantly to improving students' spiritual skills and understanding. This training not only equips students with relevant technological skills for the digital age, but also strengthens moral and ethical values that are important in daily life. However, the challenges faced include differences in students' ability levels and time constraints in integrating these programs into the school curriculum.